2014
DOI: 10.1007/s11284-014-1231-5
|View full text |Cite
|
Sign up to set email alerts
|

Cattle make two‐stage discriminations in patch choice

Abstract: Discrimination among vegetation patches differing in quantity and quality is crucial to the foraging success of grazing animals living in grasslands. Animals are assumed to discriminate preferred patches from others first, before they visit patches to eat, and then when they are eating patches. We conducted six experiments to test the ability of cattle (Bos taurus) to discriminate among vegetation patches at these two stages during foraging. In each experiment, a group of Japanese Black cows was allowed to gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Hirata et al . () showed that cattle can discriminate among vegetation patches at two stages during foraging, that is before visiting the patches and while eating the patches. The variation in the switching number among the experiments may therefore suggest that cows experienced varying degrees of difficulty in discriminating between the grasses at the two stages.…”
Section: Discussionmentioning
confidence: 99%
“…Hirata et al . () showed that cattle can discriminate among vegetation patches at two stages during foraging, that is before visiting the patches and while eating the patches. The variation in the switching number among the experiments may therefore suggest that cows experienced varying degrees of difficulty in discriminating between the grasses at the two stages.…”
Section: Discussionmentioning
confidence: 99%